POTENSI SUMBERDAYA LAHAN DI DAS BATANG BUNGO UNTUK PENGEMBANGAN SAYURAN (Land Resources Potency at Batang Bungo Watershed for Vegetables Development) - Dedy Antony; . Sunarti; Henny H. (Bioplantae, 2013)
The aim of this research is to identify watershed land characteristic at Batang Bungo and to analyze land suitability for developing commodity vegetables that were dominantly utilized by the local farmer. It is found that there are 17 land units in Batang Bungo watershed, that used to be basic data to determine sample. The research showed that rubber was the main crop and green vegetables as intercropping plant. The green vegetables were planted dominantly pepper, string beans, and eggplant. These plants were cropped among young rubber plants. The land suitability analysis showed about 55790.2 ha (74,06%) of watershed wide were suitable, the rest was not suitable that by the caused by erosion hazard.   Keywords : Characteristic, erosion, watershed.